Match performance analysis on the Chinese football association super league: A systematic review - Wang, Z.; Fang, Z.; Dai, R.; Niu, Z.; Liu, H. (International Journal of Sports Science & Coaching, 2025)
Founded in the year of 2004, the 20-year-old Chinese Football Association Super League (CSL) serves as a representative of the development of Asian football. Research focused on match performance within the CSL has gained momentum in recent years. This study provides a systematic review of match performance analysis in the CSL, detailing the analytical methods, core topics, major findings, and current research trends. Following the PRISMA 2020 guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), a structured search was conducted in the Web of Science (WOS), PubMed and Scopus databases using targeted keyword combinations, initially identifying 184 studies. After thorough screening, 45 studies were included in the review. These studies were classified into three categories: descriptive analyses, comparative analyses, and predictive analyses. Findings reveal that comparative and predictive analyses are dominant, while descriptive analysis remains essential for data contextualisation. Technical and physical performance analyses are the main research topics to date. Observations suggest the CSL is evolving toward a high-intensity style, with foreign players and substitutes playing pivotal roles. Contextual and environmental factors have been shown to substantially impact match performance. Future research will likely trend towards standardised definitions, speed zones and data, expanding studies on contextual and environmental factors with an emphasis on tactical analysis, goalkeeper performance, set-piece situations, and distinct phases of play.